The Situation of High Technology Application of Agricultural Cooperatives in Long An Province - Manh Hai, Tran; Phuong, Nguyen Thi Thu; Phuong, Mai Lan; Hien, Nguyen Thi Minh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 37 No 1, 2021)
The survey results from 8 agricultural cooperatives that have applied high technology, 5 agricultural cooperatives that have not applied high technology to their production, preservation, processing and consumption, and 5 enterprises have regular transactions with cooperatives surveyed based on questionnaires showed that high technology application has helped agricultural cooperatives in Long An province significantly improve production efficiency by being more proactive in production, reducing agricultural input costs and improving productivity and product quality. However, the scale of high techechnology applications of agricultural cooperatives is still small, scattered, high technology is mainly applied in some stages in the production process and in the crop sector due to lower capital requirements for high technology and other resource limitations of agricultural cooperatives as well as constraints on policies. Since then, the study has proposed a number of recommendations to promote agricultural cooperatives to apply high technology in agriculture more effectively.